Correlation between glans, meatus, shaft score, and penile perception after hypospadias repair - Vita Indriasari; Patricia Oktaviani Alimoeddin; Kurniawan Oki Pamungkas (Wolters Kluwer Medknow Publications, 2022)
Aims: The aim is to analyze the correlation between the degree of hypospadias based on the Glans-Urethral Meatus-Shaft (GMS) score and penile perception after hypospadias repair using pediatric penile perception score (PPPS). Settings and Design: Analytic observational study with a cross-sectional design. Subjects and Methods: Thirty-two children with hypospadias were included in this study. The severity of hypospadias was assessed using GMS score. Postoperatively, PPPS was rated by two external pediatric surgeons. Statistical Analysis Used: Correlation between GMS score and PPPS were analyzed using the Spearman test, P ≤ 0.05: Significant. Results: Mean-GMS was 8.69 ± 2.303 (mean-G 2.67 ± 0.858, mean-M 3.27 ± 0.942, mean-S 2.75 ± 1.055). Mean-PPPS was 10.19 ± 1.287. GMS score and PPPS had a very weak correlation (r = −0.227; P > 0.05). Conclusions: There was no correlation between GMS score and penile perception according to PPPS after hypospadias repair.